Mutant p53 induces Golgi tubulo-vesiculation driving a prometastatic secretome - Valeria Capaci (Nature Portfolio, 2020)
p53 mutants can promote tumorigenesis by affecting fundamental cellular pathways and functions. In this study, the authors demonstrate a novel mutant-p53/HIF1α/miR-30d axis that impacts Golgi structure, trafficking, and secretion of proteins essential for tumor growth and metastasis.